Analisis Penerapan Prinsip Good Corporate Governance Dalam Pengelolaan Dana Desa (Studi Kasus Di Desa Kedunglo Kecamatan Asembagus Kabupaten Situbondo) - Eka Rimba Putra Martha Pratama; Dwi Anggarani; Khojanah Hasan (Shofanah Media Berkah, 2023)
This research was conducted in relation to the application of the principles of good corporate governance in the management of village funds by the village government with a public sector accounting perspective in Kedunglo Village. The purpose of this study was to determine the application of the principles of good corporate governance in the management of village funds by the Kedunglo Village Government. This research was conducted because in the implementation of village accountability, the accountability carried out by the village government often experienced delays due to the lack of village apparatus in carrying out their duties in making reports on activities that had been carried out. in each record which is still difficult to understand. This research was conducted in Kedunglo Village using a qualitative descriptive approach method in the form of interviews with sources, documentation archives or photographs. there are still deficiencies that need to be fixed again. The non-optimal application of the principles of good corporate governance in the village of Kedunglo still lacks good coordination between village officials.